THE ROLE OF CYBER EXTENSION AS MEDIA INFORMATION OF PLANTATION GENETIC RESOURCES IN THE INSURANCE OF COCOA RESULTS IN SOUTH MANOKWARI REGENCY WEST PAPUA - Fangohoi, Latarus; Sugiyanto; Sukesi, Keppi; DwiCahyono, Edi (International Journal of Research -GRANTHAALAYAH, 2017)
This study aims to determine the benefits of cyber extension as a source of information on plant genetic resources in the availability of cocoa yields and the level of information adoption for farmers. The method used in this research is descriptive analysis method. Determination of research location by purposive sampling that is expansion areas that yield cocoa fruit. Census data retrieval method, using face to face technique. Extension Implementation in using cyber extension media especially on the utilization of mobile phone and Internet media in obtaining information. It also provides positive benefits in the development of extension competence, especially in utilizing cyber extension, in seeking agricultural information through Cyber extension to find information on agricultural cultivation concerning the availability of cocoa beans at the farm level. The results showed that the extent of the extension implementer in utilizing cyber extension in the category was 82% and 18% in the high category. Ownership of media information for the average trainer has a mobile phone (100%) and Media Laptop (59.09%), long became extension 5-10 years (77.27%), extension workers have the education level of SMK/SPMA (72.73%) and internet usage per day for extension workers 1-2 hours.